Systematic review of photodynamic therapy for the treatment of hidradenitis suppurativa. Issue 1 (24th July 2022) - Reshetylo, Sofiya; Narla, Shanthi; Bakker, Caitlin; Freeman, Thomas; Farah, Ronda S.; Hamzavi, Iltefat H.; Goldfarb, Noah
Abstract: Objective: To perform a systematic review of available literature regarding the use of 5‐aminolevulinic acid (ALA) and ALA derivative photodynamic therapy (PDT) in the treatment of hidradenitis suppurativa (HS) and provide recommendations on its use. Methods: A systematic review was performed of all published studies up to September 1, 2019 from nine databases, including PubMed, that evaluated PDT in the treatment of HS. For each study, quality of evidence and risk of bias was evaluated. Recommendations from the body of evidence were created based on Strength of Recommendation and Taxonomy (SORT) criteria. Results: Eighteen studies met inclusion criteria. The majority of studies had a high risk of bias. Blue light PDT with 20% ALA and red light PDT with 16% methyl aminolevulinate (MAL) demonstrated some benefit based on a small number of poor‐quality studies with a high risk of bias (Grade C, level III evidence). The most promising results were for 1%–5% ALA with intralesional diode, with good to complete response in 78%–94% of anatomic sites treated (Grade B, level II evidence). Limitations: The majority of studies contained high levels of bias, with significant heterogeneity between studies. Conclusions are limited by small samples sizes, lack of randomized controlled trials, and differing protocols. Conclusion: Further studies are needed to determine the clinical efficacy of 20% ALA with blue light and MAL with red light. Intralesional diode PDT shows the most promise and warrants further investigation in larger, randomized controlled trials.